First report of three different parasite species in two dolphin species stranded on the coast of Portugal - João T. Cruz; David W. Ramilo; Jorge Correia; Fernando Afonso; Isabel Pereira da Fonseca; Luís Cardoso; Alfonso Marzal; Marina Sequeira; Ana Falcão; Luís Madeira de Carvalho (International Journal for Parasitology: Parasites and Wildlife)
Understanding the dynamics of the interaction of marine parasites with their hosts, especially in terms of diversity, distribution and pathogenicity can be of great importance in a Global Change era. Monitoring the parasite diversity of marine mammals holds not only ecological importance but also can be of significance for public health. However, there is a scarcity of parasitological research on cetaceans in the eastern Atlantic Ocean, namely in Portugal. Here we explore the morphology, diversity and pathogenicity of parasites in two different cetaceans, Delphinus delphis (common dolphin) and Stenella coeruleoalba (striped dolphin), stranded near the coast of Lisbon, Portugal. During their necropsy, three parasite species were collected and preserved in 70 % ethanol. In the laboratory, nematodes were identified as Halocercus delphini, and tetraphyllidean merocercoids as Clistobothrium delphini and Clistobothrium grimaldii. Additionally, C. delphini specimens were classified as belonging to morphotypes B and C. To the authors' knowledge, this is the first reference of these three parasites species in Portugal. This information is critical for understanding the impact of these organisms on the health of dolphins and adds information to the parasitological fauna of these hosts.